The impact of an educational curriculum associated with tactical exercises in light of the programmed method to improve some physical abilities in handball (Journal of the College of Basic Education, 2022)
The researcher used the programmed method, which is one of the self-learning methods, to identify its impact on the learners and to provide appropriate learning opportunities through the optimal investment of effort and time.The research aims to:1- Preparing an educational curriculum using programmed instruction in learning tactical exercises in handball.2- To identify the effect of the educational curriculum prepared by the programmed learning method in improving some physical abilities in the game of handball.